Filial obligations, affect and masculinities: Vietnamese-Australian young men being and becoming good sons. Issue 3 (3rd July 2022) - Stahl, Garth; Zhao, Yang
ABSTRACT: For those working in the field of critical studies of men and masculinities (CSMM), the study of masculinities, culture and intergenerational familial responsibilities continues to be an important area of research. Drawing on a case study of five second-generation Vietnamese-Australian males over three years, we seek to explore the role of family in shaping aspirations and masculinities during the liminal time in their lives immediately following compulsory schooling. The five participants aspired to pursue a different trajectory than their parents who laboured in agriculture, factory work or as restaurant owners. The data provides insights into some of the ways in which aspirations are affectively realized in tandem with a gendered sense of Vietnamese familial responsibilities. Central to the analysis is the discursive construction of masculinity and the cultural construction of filial piety – how to be a good son. In exploring how affective familial relations inform aspirations to be a good son, we outline three overlapping dimensions – a sense of duty, sacrifice and managing conflict – before concluding with an analysis of how Vietnamese-Australian masculine subjectivities are embodied and performed.